THE IMPACT OF SILVOFISHERY CONDITIONS IN THE MANGROVE ECOSYSTEM ON THE SOCIO-ECONOMIC CONDITIONS OF THE COMMUNITY IN LUBUK KERTANG VILLAGE - Hafiz Marasoki; Syahbudin Hasibuan; Eri Yusni (CV. Radja Publika, 2024)
This research aims to determine the influence of silvofishery in the mangrove ecosystem on the socio-economic conditions of the community in Lubuk Kertang Village. The population was 1124 families, the sampling technique used slovin to obtain 100 people as research samples, the data analysis technique used path analysis with the SEM-PLS 4.0 measurement tool. The results of this research are that there is an influence between livelihoods and socio-economic conditions because the original sample value is 0.611 and p-values ​​are 0.000 < 0.05, there is an influence between income and socio-economic conditions because the original sample value is 0.354 and p-values ​​are equal to 0.000 < 0.05. Then there is no influence between education and socio-economic conditions with the original sample value of 0.041 and p-values ​​0.743 > 0.05. Livelihoods have no effect on socio-economic conditions mediated by silvofishery in the Lubuk Kertang Community, this is because the p-value is 0.182 > 0.05. In this research, income has no effect on socio-economic conditions mediated by silvofishery in the Lubuk Kertang Community, this is because the p-value is 0.214 > 0.05. Then education influences socio-economic conditions mediated by silvofishery in the Lubuk Kertang Community, this is because the p-value is 0.016 < 0.05.